Heteroarylureas with fused bicyclic diamine cores as inhibitors of fatty acid amide hydrolase. Issue 20 (15th October 2020) - Keith, John M.; Jones, William; Pierce, Joan M.; Seierstad, Mark; Palmer, James A.; Webb, Michael; Karbarz, Mark; Scott, Brian P.; Wilson, Sandy J.; Luo, Lin; Wennerholm, Michelle; Chang, Leon; et al.
Graphical abstract: Abstract: A series of mechanism-based heteroaryl urea fatty acid amide hydrolase (FAAH) inhibitors with fused bicyclic diamine cores is described. In contrast to compounds built around a piperazine core, most of the fused bicyclic diamine bearing analogs prepared exhibited greater potency against rFAAH than the human enzyme. Several compounds equipotent against both species were identified and profiled in vivo.